2018
DOI: 10.12693/aphyspola.134.783
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Commercially Pure Ti Powders Prepared by Cryogenic Milling

Abstract: Commercially pure Ti Grade 2 was prepared by cryogenic attritor milling in liquid argon under different processing conditions. Two types of milling balls: stainless steel milling balls and tungsten carbide balls were employed. The effect of processing parameters on particle size and morphology, contamination, and powder microhardness was investigated. The powder particles changed their shape from spherical to a disc/plate during milling. Reduction of particle size was only moderate, depended on time of milling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The temperature experienced by the powder during milling can also determine the nature of the final powder product. It was demonstrated that at low temperatures the dynamic recrystallization and grain growth are suppressed, thus the enhancement of grain refinement leads to an ultra-fine-grained microstructure within each powder particle [33][34][35][36][37][38][39][40]. An empirical explanation of the development of nanostructures is reported by Witkin [35]: during continued milling the increasing of dislocation density is followed by annihilation and recombination of dislocation with the formation of nanometer-scale sub-grains.…”
Section: Introductionmentioning
confidence: 99%
“…The temperature experienced by the powder during milling can also determine the nature of the final powder product. It was demonstrated that at low temperatures the dynamic recrystallization and grain growth are suppressed, thus the enhancement of grain refinement leads to an ultra-fine-grained microstructure within each powder particle [33][34][35][36][37][38][39][40]. An empirical explanation of the development of nanostructures is reported by Witkin [35]: during continued milling the increasing of dislocation density is followed by annihilation and recombination of dislocation with the formation of nanometer-scale sub-grains.…”
Section: Introductionmentioning
confidence: 99%